China’s Soft Power in Bangladesh: A Comparative Studies - Chakrovorty, Aditi (American Journal of Social Sciences and Humanities, 2020)
China is now carrying the reputation of the world’s fastest economy’s title and creating an international good image in her soft way. China’s way of creating an international image is different from the United States of America. China has its own inclusive way of flourishing. Chinese Yan-Yang philosophy makes China’s cultural inclusiveness and makes it how to balance the paradoxical situation in the international arena. The international system is changing with the passage of time. China is becoming a more influential international actor in world politics and regional power also. China’s reemergence and rejuvenation are not connected with military strategy but with China’s Soft power. China’s South Asia policy is well designed for long term strategy to follow win-win relations and that also visualized a prominent leadership role in the South Asian region. Bangladesh is Geo-politically and strategically a very prominent country. The paper is focusing on the pragmatic theory. The paper talks about Bangladesh’s perspective on China’s soft power, Bangladesh-India and China relation’s paradox which is the most important challenge for Bangladesh. Despite skeptics, the parameter of Bangladesh-China relation is gradually rising high. Soft power exchange is following President Xi Jinping’s ‘Win-Win’ projection for both Bangladesh and China. The paper is about China’s soft power in Bangladesh and mutual relations.